Manage your mind : the mental fitness guide - Butler, Gillian. (: Oxford University Press, 1995)
Gillian Butler and Tony Hope argue that for real psychological well-being, you must combine approaches - integrating techniques of management with those of psychology, mixing feeling with action and work with play. In Managing Your Mind, a ground-breaking, step-by-step guide, they show you how you can learn the skills and attitudes that will help you become more effective in your work while you enjoy a more fulfilling personal life. Just as simple measures - regular exercise, a sensible diet - can make you feel better physically, the simple strategies described in Managing Your Mind will stretch, strengthen, and tune your mind. The authors contend that without the right training, your thoughts, feelings, and behaviors can sabotage important goals and cause depression and anxiety. But with the powerful, tested techniques described here, you can cope with the rigors and stresses of everyday life, keep mentally fit, and enjoy your life to the fullest. In addition, Managing Your Mind includes specific, up-to-date information on how to strengthen your memory, quit smoking, sleep better, recover from alcohol abuse, and more.